2021
DOI: 10.1021/acs.langmuir.1c00671
|View full text |Cite
|
Sign up to set email alerts
|

pH-Mediated Aggregation-to-Separation Transition for Colloids Near Electrodes in Oscillatory Electric Fields

Abstract: Colloids in low-frequency (<1 kHz) oscillatory electric fields near planar electrodes aggregate in neutral pH electrolytes due to electrohydrodynamic (EHD) flow but separate in alkaline pH electrolytes. Colloid ζ-potential and electrolyte ion mobilities are thought to play roles in the underlying mechanism for this phenomenon, but a unifying theory for why particles aggregate in some electrolytes and separate in others remains to be established. Here, we show that increasing local pH near the electrode with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…The model solves the transient equation for conservation of ionic species. 31,45,46 Diffusion, migration and convection determine the fluxes, j i , of ionic species. The reaction term, R i , accounts for the equilibrium reaction of water and dissociation of SNARF within the liquid domain.…”
Section: Experimental Methods and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The model solves the transient equation for conservation of ionic species. 31,45,46 Diffusion, migration and convection determine the fluxes, j i , of ionic species. The reaction term, R i , accounts for the equilibrium reaction of water and dissociation of SNARF within the liquid domain.…”
Section: Experimental Methods and Analysismentioning
confidence: 99%
“…11,13,25,36 However, with some exceptions, 33,48 the effect of faradaic processes, and the ensuing gradients of electroactive species, have not been an integral part of the physical description for the forces acting on charged particles under ac electric fields. 7,31,36 An important barrier has been the need to measure concentration and fluxes of ionic species with high spatial and temporal resolution. The transport model reproduces the basic features of the experiments.…”
Section: Mechanistic Insights Into the Motion Of Particles Under Aper...mentioning
confidence: 99%
See 2 more Smart Citations
“…45 Although existing theories describe EDP for single particles with small or large zeta potentials, [24][25][26]37 possibilities for fundamental contributions exist in the context of dynamic assembly and manipulation of colloids near electrodes. 46 For example, pH gradients generated in the vicinity of planar electrodes led to the patterning of particles. 47 In another key example, Silvera Batista et al observed that when charged particles of low zeta potential were subjected to dc fields in dimethyl sulfoxide (DMSO), particles focused tens of microns away from both electrodes.…”
Section: ■ Introductionmentioning
confidence: 99%